An ePub learning module and students' mathematical reasoning ability: A development study - Hidayat, Wahyu; Rohaeti, Euis Eti; Ginanjar, Agie; Putri, Ratu Ilma Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
The mathematical reasoning ability is one of the essential hard skills of a student, especially in solving everyday problems. In supporting the achievement of this mathematical reasoning ability, meaningful teaching materials are an essential part of keeping exciting and not dull a learning process. This study aimed to design and develop an e-module in the ePub format with the problem-based learning approach to improve students' mathematical reasoning ability on arithmetic sequences and series concepts. This study used the design research method of development research in two stages—preliminary design and formal evaluation design—with tryouts performed on 32 grade XI students as research subjects. The data collection techniques used were documentation, observation, interviews, and tryouts. Data analysis was carried out quantitatively and qualitatively. The results showed that the e-module developed was valid and practical to improve students' mathematical reasoning ability, especially in solving problems related to sequences and series. The indicators of mathematical reasoning ability better improved using this ePub module were proposing problem-solving assumptions and concluding solutions logically. The development of the e-module in the e-Pub format offers alternative solutions to improve students' mathematical reasoning ability.